Analisis geopolitik dan geostrategi Indonesia dalam menghadapi persaingan ekonomi - Tyas, Naysilla Ika Yuli Setyaning (Maliki Interdisciplinary Journal, 2026)
The development of global economic competition has significantly affected the economic conditions and national resilience of many countries, including Indonesia. As a country with a strategic geographical position, Indonesia needs to implement appropriate geopolitical and geostrategic policies in order to face various global challenges. This study aims to determine the role of Indonesian geopolitics and geostrategy in dealing with global economic competition in the modern era. The research method used in this study is library research by utilizing books, national journals, and scientific articles related to the topic. The results indicate that Indonesia’s geographical position provides major opportunities in international trade and global economic cooperation. However, globalization also creates several challenges, such as increasing international market competition, dependence on foreign economies, and rapid technological development. Therefore, strengthening national strategies through improving human resources, strengthening the national economy, and utilizing technology and innovation is necessary. Through the proper implementation of geopolitics and geostrategy, Indonesia is expected to maintain national stability and improve its economic competitiveness amid globalization developments.